Nursing Diagnosis in care of patients with Renal Insufficiency Acute: Delphi Technique - Graziela Ramos Souza; Maria do Carmo Querido Avelar (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Renal failure is a major public health issue. Nurses need to be trained to intervene with these patients' problems. This is a descriptive, transversal and field study, with a quantitative approach, performed in the Intensive Care Unit of a general hospital in São Paulo, in 2007. The sample was partly composed of twelve nurses, who were the judges. To identify the nursing diagnoses (ND), according to NANDA classification taxonomy II, considered fundamental in the orientation of nursing interventions with patients prone to renal dysfunction, using the Delphi Technique. Using the three rounds, five nursing diagnoses (ND) were selected, based on the orientation of nursing interventions with patients prone to renal dysfunction. They are: Reduced Cardiac Output; Inefficient Tissular Renal Perfusion; Deficient Liquid Volume, Excessive Liquid Volume and Risk to Infection. The results meet the proposed objective; they are seen as a possibility of standardization for naming nursing issues and of the use of a unified language targeted to interventions, directing efforts to raise the quality of the assistance process to patients prone to renal dysfunction.